LIVING QUR’AN : RUTINITAS PENULISAN LAFADZ BASMALAH DI AWAL BULAN MUHARRAM ( STUDI KASUS DI PONDOK PESANTREN TURUS PANDEGLANG) - Musyarofah, Melinia Siti (Al-Fath, 2021)
This study discusses how the public's reception of the Al-Qur'an, in this case is about reviving the Qur'an in the midst of Islamic boarding school life. There are several routines that are always carried out at this Turus boarding school, including the writing of the Basmalah lafadz which is carried out on the 1st of the month of Muharram. This routine is carried out by all residents in the Islamic boarding school both from caregivers, teachers, administrators and students as well as female students. As for the procedure, namely lafadz basmalah written as many as 113 times, facing the Qibla and must have ablution. The object of research at the Turus Pandeglang Islamic Boarding School uses a phenoneological approach with the interview method